A weighted cellular automata 2D inundation model for rapid flood analysis. (October 2016) - Guidolin, Michele; Chen, Albert S.; Ghimire, Bidur; Keedwell, Edward C.; Djordjević, Slobodan; Savić, Dragan A.
Abstract: To achieve fast flood modelling for large-scale problems, a two-dimensional cellular automata based model was developed. This model employs simple transition rules and a weight-based system rather than complex Shallow Water Equations. The simplified feature of cellular automata allows the model to be implemented in parallel environments, resulting in significantly improved modelling efficiency. The model has been tested using an analytical solution and four case studies and the outputs were compared to those from a widely-used commercial physically-based hydraulic model. Results show that the model is capable of simulating water-depth and velocity variables with reasonably good agreement with the benchmark model, using only a fraction of the computational time and memory. In the case of the real world example, the proposed model run times are up to 8 times faster. The rapid and accurate attributes of the model have demonstrated its applicability for quick flood analysis in large modelling systems. Highlights: A new fast flood model using cellular automata (CA) technique has been developed. The model uses a weight-based system to minimise the use of complex equations. The parallel model implementation runs on multi-core CPUs and graphics card GPUs. The model can be faster and can use less memory than a widely-used commercial model.